2015
DOI: 10.1177/2049463715600460
|View full text |Cite
|
Sign up to set email alerts
|

Brief psychologically informed physiotherapy training is associated with changes in physiotherapists’ attitudes and beliefs towards working with people with chronic pain

Abstract: This study aimed to investigate the impact of a brief psychologically informed physiotherapy training (PIPT) course on physiotherapists' attitudes and beliefs towards working with people with chronic pain. Specifically, the training aimed to help the participants better recognise the role of psychosocial factors in chronic pain and to better target the key processes of the psychological flexibility (PF) model in their treatment interactions. A total of 26 physiotherapists working in an outpatient musculoskelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 33 publications
8
28
2
Order By: Relevance
“…In our experience, physical therapists' initial perception was that implementing PIPT strategies in (21). We observed favorable treatment orientation shifts from predominantly biomedical to biopsychosocial, following attendance at the live workshop which is consistent with previous studies where similar duration of PIPT training was delivered (26,45). Our viewpoint is that this favorable change in treatment orientation and confidence is a practical indicator that the PIPT training has potential for altering therapists' attitudes, beliefs and confidence.…”
Section: Patient-centered Communicationsupporting
confidence: 88%
“…In our experience, physical therapists' initial perception was that implementing PIPT strategies in (21). We observed favorable treatment orientation shifts from predominantly biomedical to biopsychosocial, following attendance at the live workshop which is consistent with previous studies where similar duration of PIPT training was delivered (26,45). Our viewpoint is that this favorable change in treatment orientation and confidence is a practical indicator that the PIPT training has potential for altering therapists' attitudes, beliefs and confidence.…”
Section: Patient-centered Communicationsupporting
confidence: 88%
“…In our experience, physical therapists' initial perception was that implementing PIPT strategies in "buy-in" for treatment [29]. We observed favorable treatment orientation shifts from predominantly biomedical to biopsychosocial following attendance at the live workshop which is consistent with previous studies where similar duration of PIPT training was delivered [26,42]. Our viewpoint was that this favorable change in treatment orientation and confidence is a practical indicator that the PIPT training has potential for altering therapist attitudes, beliefs and confidence.…”
Section: Patient-centered Communicationsupporting
confidence: 85%
“…A qualitative study evaluated LBP interventions with a biopsychosocial focus found that 13 qualified PTs experienced improved confidence to manage the biopsychosocial dimensions after an average of nine workshops with cognitive Abbreviations: SD Standard Deviation, CI Confidence Interval, η p 2 Partial Eta Squared, PCS Practitioner Self-Confidence Scale (score 4-20, lower score indicates higher self-confidence), PABS-PT Pain Attitudes and Beliefs Scale for Physiotherapists, BM Biomedical orientation (score 10-60 indicates higher score higher orientation), BPS Biopsychosocial orientation (score 9-54, indicates higher score higher orientation) Abbreviations: SD Standard Deviation, CI Confidence Interval, η p 2 Partial Eta Squared, COM-B "Capability", "Opportunity", "Motivation" and "Behaviour" model functional therapy training [54]. Furthermore, a voluntarily 8-day university course [55] as well as a 7-h PT workshop [56] focusing on biopsychosocial treatment showed a similar result as in the current study. These three studies [54][55][56] however only performed follow-up directly after the training/course leaving long-term effects unclear.…”
Section: Discussionmentioning
confidence: 99%